Bridge the Partisan Divide and Develop Effective Policies with Systems Engineering. Issue 3 (6th October 2021) - Hartung, Jim
ABSTRACT: The United States is a divided country. This is sometimes a strength when we consider diverse viewpoints before deciding. However, it is often a weakness, when hyper‐partisan politics divides us and prevents us from addressing serious problems. In this article I discuss how lawmakers and policymakers can use systems engineering to bridge the partisan divide and develop practical, nonpartisan solutions for complex societal problems. First, I describe a simple six‐step systems engineering process for optimizing social, economic, and political systems. Second, I illustrate this process with two examples: (1) development of a nonpartisan tax reform proposal that balances the federal budget and addresses key societal problems without increasing the economic burden on taxpayers and (2) development of a nonpartisan plan for the United States to achieve the United Nations Sustainable Development Goals and address other urgent problems. Third, I discuss how lawmakers and policymakers can incorporate systems engineering into the lawmaking process. Although this article uses the United States as an example, many of the ideas presented here also apply to other countries.